PENEGAKAN HUKUM TERHADAP TINDAK PIDANA PENCABULAN YANG DILAKUKAN OLEH ANAK BERDASARKAN UNDANG-UNDANG NOMOR 35 TAHUN 2014 TENTANG PERUBAHAN ATAS UNDANG-UNDANG NOMOR 23 TAHUN 2002 TENTANG PERLINDUNGAN ANAK DI POLRESTA PEKANBARU - Simanjuntak, Raynanda; Effendi, Erdianto; Edorita, Widia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
The child is part of a younger generation that is a potential successor to the idealsof the struggle of a nation that has a strategic role and has the characteristics and specialnature, require the guidance and protection in order to ensure the physical growth, mentaland social as a whole, harmonious and balanced, So it needs optimally protected by thestate. The purpose of this thesis, namely: First, How law enforcement against criminalacts of sexual abuse committed by a child under Law No 35 of 2014 on the Amendment ofAct No. 23 of 2002 on Child Protection in Pekanbaru Police, Second, Do constraints inlaw enforcement against criminal acts of sexual abuse committed by a child under LawNo. 35 of 2014 on the Amendment of Act No. 23 of 2002 on Child Protection in PekanbaruPolice, Third, How does the effort to overcome the obstacles in law enforcement againstcriminal acts of abuse which performed by children based on Law No. 35 of 2014 on theAmendment of Act No. 23 of 2002 on Child Protection in Pekanbaru Police.This type of research can be classified into types of sociological research. This typeof research is descriptive analysis. Source of data used were obtained through three (3)legal materials are the primary legal materials, secondary and tertiary.The datacollection techniques were done using two methods namely interview and study ofliterature.From the results of research and discussion, there are three main things that can beinferred. First, Law Enforcement for criminal acts of sexual abuse committed by childrenagainst children in Pekanbaru City Police have been running smoothly as it should be,and are in accordance with the legislation in force. But it is still not perfect because thereare some cases that did not complete his case. Secondly, As for the factors inhibitingPekanbaru City Police in handling criminal cases of sexual abuse against childreninclude evidence, the victim does not want to report the crime of sexual abuse, the suspectfled and perpetrators of abuse are still under age. Third, efforts were made to overcomethe obstacles in handling criminal cases of sexual abuse against children includesConducting post mortem on the victim, Call or Come Victim, Seek and publishes wantedlist, Doing diversion to the accused under umur.Saran, First, order the police whohandled the case criminal acts of sexual abuse committed by children against children isbetter implement the Child Protection Act. Second, protect the public order police more sothat cases like this do not happen again. Third, the order for the parents more aware ofthe kejatan-crime that occurs in children.Keywords : Law Enforcement - Crime of Abuse - Child